UJI DAYA SIMPAN DAN MUTU GIZI CAKE BOLU KUKUS DENGAN PENAMBAHAN BUAH PEPAYA - Mohamad Ucil Katili; Novian Swasono Hadi; Lien A. Ntau (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2020)
ABSTRACT Sweet cake (bolu in the Indonesia language) is a bread-like baked (sometimes steamed) dessert, which is made from various combinations of flour, egg, and other ingredients. Papaya, which is mostly consumed straight, cam be an additional ingredient of steamed sweet cake. The objective of this research was to explore the storability and nutrition of sweet cake with papaya. Repling on the experimental method, this research employed a completely randomized design with four treatments. The results revealed that the steamed sweet cake lasted for one to three days at room temperature, the cake could last up to four days if it stored in a refrigatore. Nutrition contents of the cake in treatment P0 (0%) comprised energy (1,313 grams), protein (12.1 grams), fat (51.1 grams), and carbohydrate (206.0 grams). In treatment P1 (25%), the contents were energy(1,333,3 grams), protein (12.4 grams), fat (51.2 grams), and carbohydrate (210.9 grams). In the P2 (50%), the contents were energy (91,352.8 grams), protein (12.7 grams), fat (51.2 grams), and carbohydrate (215.8 grams). In treatment P3 (85%), the contents were energy (1,391.8 grams), protein (13.3 grams), fat ( 51.3 grams) and carbohydrate (225.6 grams). People are encouraged to consider papaya as an additional ingredient to processed food or snacks for people, ranging from children, adolescents, adults, and old adults. ABSTRAK Bolukukusadalah jenisboluyang terbuat dari bahan seperti telur, ditambahkan tepung dan bahan lainnya yang dimasak dengan cara dikukus. Selain tepung dan bahan utama pembuatan bolu kukus, buah pepaya yang hanya dijadikan buah sajian biasa, bisa dijadikan sebagai bahan penambah olahan cake bolu kukus. Adapun tujuan dari penelitian ini adalah untuk mengetahui uji daya simpan dan mutu gizi cake bolu kukus dengan penambahan buah pepaya. Penelitian ini merupakan penelitian eksperimen dengan rancangan acak lengkap menggunakan 4 perlakuan. Hasil masa simpan yang di dapat cake bolu kukus pada suhu ruang hanya bisa bertahan 1-3 hari, sedangkan pada suhu refrigator Bolu kukus bisa bertahan sampai 4 hari. Dan hasil kandungan nilai gizi cake bolu kukus pada P0(0%) yaituenergi1,313.8gram, protein 12,1gram, lemak 51,1gram,karbohidrat 206,0 gram. P1(25%) energi 1,333,3gram, protein 12,4gram,lemak 51,2gram,dan karbohidrat 210,9gram.P2(50%)energi 1,352.8 gram, protein 12,7 gram, lemak 51,2 gram,dan karbohidrat 215,8 ram.P3(85%)yaitu energi 1,391.8gram, protein 13,3gram, lemak 51,3gram, karbohidrat 225,6gram. Disarankan pada masyarakat agar dapat memanfaatkan buah papaya dalam pembuatan olahan makanan jenis lainya serta dijadikan sebagai jajanan untuk semua golongan umur, yaitu anak-anak, remaja, dewasa, orang tua maupun untuk lanjut usia.